Jaminan Pemberian Pesangon Terhadap Karyawan Yang Terdampak Pemutusan Hubungan Kerja (PHK): Studi Kasus PHK Massal Shopee Indonesia Tahun 2023 - Zahranisza, Ayzza Rachma; Fakhira, Regita; Safitri, Zahra Awaliany; Fachri, Amanda Maharani (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Termination of Employment  is a common event that occurs in the employment sector. The provisions for layoffs are regulated in Law Number 13 of 2003. This research aims to analyze the guarantee mechanism for providing severance pay to employees affected by termination of employment and analyze the level of company compliance in providing severance pay to employees affected by termination of employment using normative juridical methods. The results of the research explain the termination of employment relations that occurred in Indonesia, which highlights the case of mass termination of employment relations that occurred at Shopee Indonesia. The layoffs carried out by this company went well and in accordance with the laws in force in Indonesia, including the severance pay received by workers affected by the layoffs. Based on this, it can be concluded that the implementation of the rules regarding layoffs is quite good, although there are still efforts to continue to address this issue.